THE DETERMINANTS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND IMPLICATIONS TOWARD HOSPITAL SERVICE QUALITY - Rina Susanti Hartono (Business and Entrepreneurial Review, 2015)
The objective of this research is to analyze the factors that of influence ofEmotional Intelligence, Emptional Labor and Transformational Leadership on Organizational Citizenship Behavior/OCB and Service Quality.The study population number of 2,721 medical and paramedical personnel Hospital in Bekasi.The method used is descriptive survey and explanatory survey with a sample size 356 respondents, while the data analysis method used is Structural Equation Model (SEM).The results showed that Emotional Intelligence, Emotional Labor, and Transformational Leadership partially and together positive and significant impact on OCB with a contribution of 46%. Furthermore Emotional Intelligence, Emotional Labor, Transformational Leadership, and OCB partially or jointly positive and significant impact on Service Quality, with a contribution of 75%.Organizational Citizenship Behavior or partial OCB most dominant influence Service Quality.The model proposed in the study showed a positive effect of Emotional Intelligence, Emotional labor and Transformational Leadership on Service Quality through Organizational Citizenship Behavior.Suggestions for further research can analyze the influence of Organizational Citizenship Behavior towards another set of variables such as customer satisfaction, consumer confidence and consumer loyalty with Service Quality as an intervening variable.Research shows that the variable Organizational Citizenship Behavior with strong mediating variables influence Emotional Intelligence, Emotional labor and Transformational Leadership on Service Quality Medical and Paramedical Hospital in Bekasi.This model can be used as a useful instrument for Hospital Leaders in developing and improving Service Quality through improved behavior of medical personnel and paramedics Hospital based on the relationship between Emotional Intelligence, Emotional labor and Transformational Leadership.